Smith's anesthesia for infants and children - Davis, Peter J. (Anesthesiologist); Cladis, Franklyn P.; Motoyama, Etsuro K. (Elsevier, 2011)
This 8th Edition, edited by Drs. Peter J. Davis, Franklyn P. Cladis, and Etsuro K. Motoyama, delivers all the state-of-the-art guidance you need to provide optimal perioperative care for any type of pediatric surgery. Gain new insight into today's hottest topics, including sleep-disordered breathing, cuffed endotracheal tubes, premedication, emergence agitation, postoperative vomiting, and new airway devices. Stay current with new chapters on ICU management, conjoined twins, and basic neonatal physiology, plus new coverage of pharmacology and monitoring techniques. Get outstanding visual guidance with full-color illustrations throughout the book.